Adult onset Still's disease: Clinical features and outcome in 16 Thai patients - Louthrenoo W. (2014)
The clinical features of adult onset Still's disease (AOSD) have rarely been described in Thai patients. We report the clinical manifestations, laboratory findings, and outcome of 16 Thai patients with AOSD, and compare these findings with those of the western and other oriental series. Fourteen patients (87.5%) had the onset of their disease between 16-35 years of age. The most common features presented were fever (100%), arthralgia and myalgia (100%), significant weight loss (84.6%), arthritis (81.3%), skin rashes (68.8%), sore throat (62.5%), elevated erythrocyte sedimentation rate (100%), leukocytosis (93.8%), and liver dysfunction (75%). Pleuro-pericarditis and abdominal pain were uncommon. All but 2 patients required corticosteroids to control their systemic disease activity. The clinical course of 13 patients, who were followed for more than 12 months, was monocyclic systemic disease in four cases, polycyclic systemic disease in five, chronic articular monocyclic systemic in one, and chronic articular polycyclic systemic in three. When compared with western and other oriental series, the AOSD in Thai patients shared similar clinical features and laboratory findings, suggesting that mechanisms of pathogenesis may be similar in patients from widely different genetic backgrounds and geographic locations. Corticosteroids were frequently required and dramatically effective.